(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The present study was carried out to investigate the analgesic, anti-inflammatory, antibacterial and antifungal properties of ethanol leave extract of Mangifera indica. For evaluation of analgesic and anti-inflammatory properties, acetic acid induced writhing response model and carrageenan induced paw edema model were used in Swiss albino mice and Wistar albino rats, respectively. In both cases, leaves extract were administered and the obtained effects were compared with commercially available analgesic and anti-inflammatory drug, Diclofenac Sodium. In analgesic bioassay, oral administration of the ethanol leaves extract significantly (P<0.01) reduced the writhing response. The degree of inhibition of leaves extract was 55.8% compared to the effect of standard analgesic drug, Diclofenac Sodium (75.28%). On the other hand, though leaves extract reduce paw edema but they did not show any significant effect. The antibacterial and antifungal activity of leaves extract also carried out by disc diffusion technique and poisoned food technique. In antibacterial experiment, leaves extract showed 7.0 mm to 11.5 mm in diameter of zone of inhibition against six Gram positive bacteria (such as Staphylococcus aureus, Streptococcus agalactiae, Bacillus cereus, Bacillus megaterium, Bacillus subtilis and Lactobacillus vulgaricus) and two Gram negative bacteria (such as Shigella flexneri and Shigella sonei ). But Salmonella typhi and Proteus sp had negative activity on leaves extract. The leaves extract of Mangifera indica showed antifungal activity against three fungal species (such as Aspergillus ustus, Aspergillus niger and Aspergillus ochraceus). Keywords: Mangifera indica; Analgesic; Anti-inflammatory; Antibacterial; Antifungal DOI: 10.3329/jbau.v8i2.7932 J. Bangladesh Agril. Univ. 8(2): 239-244, 2010